Less Developed Countries: Success in Efforts to Remedy Debts? - Hildebrandová, Marika, 1982- (2008)
The aim of the dissertation is to analyse progress and preset state of debt relief. It may be argued that developing countries have not been very successful in promoting debt forgiveness or a substantial reduction of debt stock. The reasons for this belief are that a lot of states, especially in sub-Saharan Africa, are still struggling with scarce resources to service their debts, and that there has been a number of proposals and initiatives to improve the situation the helpfulness of which may be disputed. Furthermore, debt relief so far has been granted only to a few countries in need. The dissertation will therefore present arguments why the main debt relief initiatives are not regarded as successful as they could have been, and what the reasons of slow and limited progress of debt relief may be.